Phase-Resolved Lockdown Features of Pollution Parameters Over an Urban and Adjoining Rural Region During COVID-19 - Sonbawne, Sunil M.; Fadnavis, Suvarna; Vijayakumar, K.; Devara, Panuganti C. S.; Chavan, Prashant (Frontiers in Environmental Science, 2022)
In this paper, we investigate the temporal variations in columnar aerosol pollutants and their possible association with the simultaneously measured black carbon (BC) aerosol mass concentration and associated biomass burning (BB) over urban (Delhi) and rural (Panchgaon) sites during the lockdown phases of the COVID-19 pandemic. We also show the impact of lockdown measures on ozone and its primary precursor NO2 and water vapor (H2O), a potent greenhouse gas that destroys protective ozone. For this purpose, we used multiple datasets, namely, BC aerosol mass concentration and BB aerosols from Aethalometer at Amity University Haryana (AUH), Panchgaon, India and satellite retrievals from NASA’s MODIS and OMI at both the stations. The analysis is conducted during the pre- lockdown period (1-25 March), lockdown 1st phase (25 March-14 April), lockdown 2nd phase (15 April-3 May), lockdown 3rd phase (4-17 May), lockdown 4th phase (18-31 May) and post-lockdown (1-30 June) period in 2020. Our diagnostic analysis shows substantial reduction in AOD (Delhi: -20% to -80%, Panchgaon: -20% to -80%) and NO2 (Delhi: -10% to -42.03%, Panchgaon -10% to -46.54%) in comparison with climatology (2010-2019) during all four phases of lockdown. Reduction in AOD is attributed to lockdown measures and less transport of dust from west Asian than climatology. Interestingly, despite a reduction in NO2, there is an increase in ozone amount (Delhi: 1% to 8% and Panchgaon: 1% to 10%) during lockdown I, II and III phases. The observed enhancement in ozone may be resultant from the complex photochemical processes that involve the presence of NO2, CO, Volatile Organic Compounds (VOCs) and water vapor. Interestingly, the reduction in AOD and NO2 and enhancement in ozone are stronger at rural site, Panchgaon than urban station, Delhi, indicating rural station is more benefit from improved air quality than urban station.